Evaluasi indeks loka pada tegakan Acacia mangium Willd. Di HTI PT. Arara abadi Propinsi Riau=The Evaluation of Site Index in the Stand of Acacia mangium - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
One of the objectives in developing Industrial Vegetation Forest (IVF) is to increase the forest productivity in the production forest area so that it is hoped that the high production will suffice the increasing need of timber material either for fiber timber or for carpentry. To achieve the high productivity, efforts should be conducted to approach some aspects of growth influencing the increments of productivity. The study of site index A. mangium Wild. stand is, therefore, needed to be conducted. The objectives of this study is to examine the correlation b- etween growth and production, and between soil characteristics and growth of A. mangium Wild. The study was conducted in the region of BKPH Minas, KPH Dumai where HTI PT. Arara Abadi as a supplier of raw material of PT. Indah Kiat Pulp and Paper Corporation of Riau Province was located. The results show that there was a correlation between grOwth and production of A. mangium. From eight variables observed, the most influential ones were clay content, soil pH, and available phosphate content which have determination coefficient values (R2) 0.8897 for height growth, and 0.8666 for diameter growth. These determination coefficient showed that the model could only explain 88.97 % and 88.66 % of its growth aspects. Whereas their remainders 11.03 % and 13.34 % could be influenced by other factors not available in the model. The location evaluation of index site based on the relationship between age and growth of A. mangium therefore the site was included in good site.